1995
DOI: 10.1074/jbc.270.12.6997
|View full text |Cite
|
Sign up to set email alerts
|

Endothelin Receptor Subtype B Mediates Autoinduction of Endothelin-1 in Rat Mesangial Cells

Abstract: Autoinduction of endothelin-1 (ET-1) has been suggested to be involved in the profound and long-lasting effects of ET-1. We examined mechanisms that underlie autoinduction of ET-1 in cultured rat glomerular mesangial cells. Incubation of mesangial cells with ET-1 resulted in an immediate and dose-dependent stimulation of preproET-1 mRNA expression as assessed by polymerase chain reaction coupled with reverse transcription. Within 1 h of exposure to ET-1 (10(-7) M), preproET-1 mRNA expression was increased to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
30
0
4

Year Published

1995
1995
2011
2011

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(37 citation statements)
references
References 57 publications
3
30
0
4
Order By: Relevance
“…Similar increases in ET B gene expression have been reported in the pulmonary arteries of patients with chronic thromboembolic pulmonary hypertension (44). The ET B signaling pathway has been linked to the regulation of ppET-1 gene expression in rat mesangial cells (19). The present study confirms this notion since, in a previous study, we showed that ppET-1 gene expression in the main pulmonary artery was decreased in hypertensive sheep compared with controls.…”
Section: Discussionsupporting
confidence: 80%
“…Similar increases in ET B gene expression have been reported in the pulmonary arteries of patients with chronic thromboembolic pulmonary hypertension (44). The ET B signaling pathway has been linked to the regulation of ppET-1 gene expression in rat mesangial cells (19). The present study confirms this notion since, in a previous study, we showed that ppET-1 gene expression in the main pulmonary artery was decreased in hypertensive sheep compared with controls.…”
Section: Discussionsupporting
confidence: 80%
“…A previous study reported that a blockade of ETAR that was able to activate Gαq did not inhibit ET-1 production stimulated by ET-1 in rat mesangial cells (29). On the other hand, in a study using a rat model of congestive heart failure, the ETAR antagonist BQ-123 normalized the increased expression level of ppET-1 mRNA (32).…”
Section: Discussionmentioning
confidence: 98%
“…Because of its vasoconstrictor and growth-promoting action, numerous studies indicate that ET-1 is involved in the pathogenesis of a broad spectrum of renal and cardiovascular diseases (21,22,(25)(26)(27). Previous studies have demonstrated that ET-1 induced ET-1 production through ETAR and/or ETBR-mediated pathways, suggesting that a sustained ET-1 autocrine loop contributes to the progression of cardiovascular and renal diseases (28)(29)(30)(31)(32).…”
Section: Introductionmentioning
confidence: 99%
“…Whereas ET-A receptors (ETA) mediate vasoconstriction, mononuclear cell infiltration, and production of matrix proteins (1), ET-B receptors (ETB) on endothelial cells mediate endothelium-dependent vasorelaxation via nitric oxide (NO) and prostacyclin formation (2). Several other functions are also attributed to ETB, including regulation of renal sodium (Na ϩ ) and water excretion (3) and stimulation of ET-1 gene expression (4). Taking these biologic actions into consideration, it is not surprising to regard ET-1 as one of the important mediators for the progression of chronic renal injury (5,6).…”
mentioning
confidence: 99%